Getting stuck!: Using monosignatures to test highly ionizing particles - Englert, Christoph; Jaeckel, Joerg (Physics letters, 2017)
In this paper we argue that monojet and monophoton searches can be a sensitive test of very highly ionizing particles such as particles with charges ≳150e and more generally particles that do not reach the outer parts of the detector. 8 TeV monojet data from the CMS experiment excludes such objects with masses in the range ≲650 GeV and charges ≳100e. This nicely complements searches for highly ionizing objects at ALICE, ATLAS, CMS and LHCb. Expected improvements in these channels will extend the sensitivity range to m≲750 GeV. This search strategy can directly be generalised to other particles that strongly interact with the detector material, such as e.g. magnetic monopoles.
Gesehen am 24.11.2017